Investigação das propriedades mecânicas dos compósitos de resina poliéster insaturada reforçados com fibras de bambu natural e modificadas superficialmente - Buson, Raianne Ferreira (2018)
The search for sustainability has encouraged the creation of new resources that use natural in their composition, which good properties, low cost of search and do not harm the environment. Bamboo fiber has been widely studied as a composite reinforcement because it offers lightness and mechanical resistance to the final product, replacing the use of raw materials made from petroleum. The objective of the present work is the treatment and characterization of bamboo fibers and, finally, their application in polymeric composites as a reinforcing agent. Surface treatments of alkalinization and acetylation were carried out on the bamboo fibers, and the fibers were then characterized by chemical, physical, thermal, mechanical, and morphological tests. After the incorporation of the fibers in the polymer matrix of unsaturated polyester with 10%, 20%, and 30% of fibers, the composites were analyzed by water absorption, density, scanning electron microscopy, mechanical tensile, and Izod impact. Through the FTIR, it was possible to verify the efficiency of the treatments performed, due to the growth of the band corresponding to the carbonyl group, indicating that the acetylated fiber was more hydrophobic, consonant with the water absorption test, where an acetylated fiber absorbed less water than as much. When acetylated, the bamboo fiber gained thermal stability of approximately 60oC and, through the MEV, an increase of fiber roughness was observed, evidencing the improvement in fiber / matrix adhesion. The results of the mechanical properties of traction in the fibers corroborate with those found in the x-ray diffraction test, being higher for the alkaline fiber and smaller for the acetylated fiber, which lost mechanical resistance due to acid treatment. The mechanical properties of traction and impact of the composites improved with the increase of the incorporated fiber content, concluding that they acted as reinforcement in the composites. The best mechanical tensile performance was of the composite with 30% of alkaline fiber, reinforcing the maximum tension in more than 185%. Through the SEM in the composites, the improvement of the fiber / matrix adhesion after the treatments was verified, where the presence of resin on the fibers and resin shear was noticed. For the Izod impact test, the composites with acetylated fiber obtained higher impact energy than the others, a fact justified by the better fiber / matrix adhesion, a fact that proves the effectiveness of the treatment by acetylation.